Premortem Skin Biopsy Assessing Microthrombi, Interferon Type I Antiviral and Regulatory Proteins, and Complement Deposition Correlates with Coronavirus Disease 2019 Clinical Stage - Laurence, Jeffrey; Nuovo, Gerard; Racine-Brzostek, Sabrina E.; Seshadri, Madhav; Elhadad, Sonia; Crowson, A. Neil; Mulvey, J. Justin; Harp, Joanna; Ahamed, Jasimuddin; Magro, Cynthia (The American journal of pathology, 2022)
Apart from autopsy, tissue correlates of coronavirus disease 2019 (COVID-19) clinical stage are lacking. In the current study, cutaneous punch biopsy specimens of 15 individuals with severe/critical COVID-19 and six with mild/moderate COVID-19 were examined. Evidence for arterial and venous microthrombi, deposition of C5b-9 and MASP2 (representative of alternative and lectin complement pathways, respectively), and differential expression of interferon type I–driven antiviral protein MxA (myxovirus resistance A) versus SIN3A, a promoter of interferon type I–based proinflammatory signaling, were assessed. Control subjects included nine patients with sepsis-related acute respiratory distress syndrome (ARDS) and/or acute kidney injury (AKI) pre–COVID-19. Microthrombi were detected in 13 (87%) of 15 patients with severe/critical COVID-19 versus zero of six patients with mild/moderate COVID-19 (P < 0.001) and none of the nine patients with pre–COVID-19 ARDS/AKI (P < 0.001). Cells lining the microvasculature staining for spike protein of severe acute respiratory syndrome coronavirus 2, the etiologic agent of COVID-19, also expressed tissue factor. C5b-9 deposition occurred in 13 (87%) of 15 patients with severe/critical COVID-19 versus zero of six patients with mild/moderate COVID-19 (P < 0.001) and none of the nine patients with pre–COVID-19 ARDS/AKI (P < 0.001). MASP2 deposition was also restricted to severe/critical COVID-19 cases. MxA expression occurred in all six mild/moderate versus two (15%) of 13 severe/critical cases (P < 0.001) of COVID-19. In contrast, SIN3A was restricted to severe/critical COVID-19 cases co-localizing with severe acute respiratory syndrome coronavirus 2 spike protein. SIN3A was also elevated in plasma of patients with severe/critical COVID-19 versus control subjects (P ≤ 0.02). In conclusion, the study identified premortem tissue correlates of COVID-19 clinical stage using skin. If validated in a longitudinal cohort, this approach could identify individuals at risk for disease progression and enable targeted interventions.